The Relationship between Learning Motivation and Self-Confidence with Entrepreneurial Interest in UNIMED Culinary Education Students - Putri, Selvia Alyssa; Santika, Windi; Ingtyas, Fatma Tresno; Ginting, Laurena (Journal Corner of Education, Linguistics, and Literature, 2024)
Interest in entrepreneurship among students is an important indicator of the success of entrepreneurship education in higher education. This research aims to analyze the relationship between learning motivation, self-confidence, and interest in entrepreneurship among Medan State University Culinary Education students using a quantitative survey method. The research sample consisted of 91 respondents from a total population of 91 culinary education students at Medan State University Stambuk 2022, using a total sampling technique. The data processing method is descriptive statistical analysis and Pearson correlation test. Interest in entrepreneurship among students is an indicator of the success of entrepreneurship education in higher education. This research analyzes the relationship between learning motivation, self-confidence and interest in entrepreneurship in 91 Culinary Education students at Medan State University using a quantitative approach with a questionnaire survey. The results of descriptive analysis show an average of Learning Motivation 35.72 (76.0%), Self-Confidence 34.78 (73.9%), and Entrepreneurial Interest 36.42 (77.5%). Motivation to learn and interest in entrepreneurship are relatively high and consistent, while self-confidence varies more.